Analisis Kebijakan Pengelolaan Guru di Indonesia - Widiarto, Agus (Pusat Penelitian Badan Keahlian DPR RI, 2020)
This policy analysis aims to examine the problems associated with teacher management nationally and formulate some comprehensive teacher management policy recommendations with reference to the achievement of the objectives of teacher management as professional staff. As a professional, the role of the teacher is very important, namely implementing the national education system and realizing national education goals. The function and purpose of education are the development of the potential of students to become human beings who have faith and are devoted to God Almighty, have good character, are healthy, knowledgeable, capable, creative, independent, and become citizens who are democratic and responsible. Thus, the position of the teacher as a professional becomes very strategic as one of the elements in achieving the objectives of the national education system. This policy analysis also examines the design of teacher management in terms of the division of authority between the central and regional governments according to Law No. 23 of 2014 on Regional Government and Law No. 14 of 2005 on Teachers and Lecturers.This study uses a model of policy analysis process that starts from the analysis of the formulation or design of the policy, problems in the implementation, and evaluation of the policy.Â AbstrakThis policy analysis aims to examine the problems associated with teacher management nationally and formulate some comprehensive teacher management policy recommendations with reference to the achievement of the objectives of teacher management as professional staff. As a professional, the role of the teacher is very important, namely implementing the national education system and realizing national education goals. The function and purpose of education are the development of the potential of students to become human beings who have faith and are devoted to God Almighty, have good character, are healthy, knowledgeable, capable, creative, independent, and become citizens who are democratic and responsible. Thus, the position of the teacher as a professional becomes very strategic as one of the elements in achieving the objectives of the national education system. This policy analysis also examines the design of teacher management in terms of the division of authority between the central and regional governments according to Law No. 23 of 2014 on Regional Government and Law No. 14 of 2005 on Teachers and Lecturers.This study uses a model of policy analysis process that starts from the analysis of the formulation or design of the policy, problems in the implementation, and evaluation of the policy.